Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Quality Improvement, Parents Centered Care" - --- Various Authors (Journal of Pediatric and Neonatal Individualized Medicine, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017